INVESTIGATION OF DYNAMICAL AND OPTICAL PROPERTIES OF DUSTY PLASMA IN CAPACITIVE RADIO FREQUENCY DISCHARGE OF ARGON - Ramazanov, T. S.; Daniyarov, T. T.; Dosbolayev, M. K.; Baimbetov, F. B.; Orazbaev, S. A.; Zhumanov, K. B.; Utegenov, A. U.; Azharonok, V. V.; Filatova, I. I.; Krat'ko, L. E. (Recent Contributions to Physics, 2009)
In present paper the results of the experimental investigations of dynamical and optical properties of dusty plasma in capacitive radio frequency discharge were presented. The dependence of distribution velocity dust particles versus discharge power was derived. The temperature and electron density of background gas were defined. Results of present work can be used in the further investigations of other dynamical and optical properties of dusty plasma.